2021
DOI: 10.1074/jbc.ra120.015401
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic mechanism of vitamin K epoxide reduction in a cellular environment

Abstract: Vitamin K epoxide reductases (VKORs) constitute a major family of integral membrane thiol oxidoreductases. In humans, VKOR sustains blood coagulation and bone mineralization through the vitamin K cycle. Previous chemical models assumed that the catalysis of human VKOR (hVKOR) starts from a fully reduced active site. This state, however, constitutes only a minor cellular fraction (5.6%). Thus, the mechanism whereby hVKOR catalysis is carried out in the cellular environment remains largely unknown. Here we use q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Compared to engineered SsVKOR, HsVKOR also contains additional structural features, such as the helical extension of TM1 [23], that we have not explored. Finally, the redox potential of catalytic cysteines in the engineered SsVKOR and HsVKOR can be different, which will result in different levels of active site cysteines in reduced state that contributes to a large portion of overall HsVKOR activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to engineered SsVKOR, HsVKOR also contains additional structural features, such as the helical extension of TM1 [23], that we have not explored. Finally, the redox potential of catalytic cysteines in the engineered SsVKOR and HsVKOR can be different, which will result in different levels of active site cysteines in reduced state that contributes to a large portion of overall HsVKOR activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between MS and biochemical data suggested that the PO and R states contribute about equally to the cellular HsVKOR activity. 87 Although the R state is of low abundance, its specific activity is approximately 8-fold higher than the PO state. 87 The complicated interplay between warfarin inhibition and catalysis underlies warfarin response (Figure 3C).…”
Section: Vkor Catalysis and Warfarin Inhibition Act On Different Cell...mentioning
confidence: 99%
“…For the KO binding, protection of Cys16 and Cys85 was observed only with Cys43Ala mutation that stabilizes the PO state (Figure 3B). 69,87 The wild‐type HsVKOR does not show this protection effect, probably because the catalysis continuously resolves the PO state. Unlike warfarin inhibition, HsVKOR catalysis is inactive at the O state because this reductase is fully oxidized.…”
Section: Cellular and Structural Mechanisms Of Vitamin K Antagonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This result facilitates the construction of warfarin‐hVKOR model from MD simulations. Further NEM footprinting analysis of hVKOR with its substrate vitamin K epoxide elucidates the reactive states of hVKOR in the cellular environment [97].…”
Section: Ms‐based Techniques For Footprinting Mpsmentioning
confidence: 99%